SUPERVISI KEPALA SEKOLAH TERHADAP KINERJA GURU SD NEGERI SEKECAMATAN METRO BARAT: Penelitian Tindakan Kelas - Nur, Anisa; Riswandi; Luthvi Azizah, Alif; Nurwahidin, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to determine the influence of principal supervision on the performance of State Elementary School teachers in SD Negeri Sekecamatan Metro Barat. This type of research is ex post facto. The research population is 103 teachers and the research sample is 82 teachers. The sampling technique in this study uses a non-probability technique, namely cluster sampling. The data collection technique uses questionnaires. The data analysis uses a simple linear regression formula. The results showed that there was a significant influence between the supervision of the principal on teacher performance with an F count of calculation = 74.533 with a significance level of 0.001< 0.05. Thus, the contribution of variable X to variable Y is 48.2%, the remaining 51.8% is influenced by other factors outside the study.